Pengembangan Flipbook Pedoman Kegiatan Forum Annisa Berbasis Mentoring Untuk Sekolah Menengah Pertama - Zilfadhliyah; Sirajul Munir; Yanti Mulia Roza (JURNAL ARMADA PENDIDIKAN, 2026)
The implementation of Annisa Forum activities in schools is often hampered by the lack of a systematic and easily accessible digital guidebook. The absence of this guideline causes activities to run undirected and unsustainable, making it difficult to achieve the goal of developing Muslim women's character. This study aims to produce a valid and practical mentoring-based Annisa Forum guidebook, designed in the form of a digital flipbook. The research method uses the 4D Research and Development (R&D) model (Define, Design, Develop, Disseminate) which is limited to the Develop stage. The Define stage includes needs analysis, the Design stage includes the design of digital materials and formats, and the Develop stage involves expert validation and practicality testing. This research was conducted at SMPN 2 Batusangkar. The research subjects included three expert validators (materials, media, and language), the Forum mentor teacherAnnisa, and 43 female students involved in a limited trial. Data collection techniques included observation, interviews, documentation, expert validation, and questionnaires. The validation results showed a percentage of 88% (very valid) with material aspects of 89.33%, media 86.67%, and language 86.67%. The teacher's practicality test reached 90.33% and student responses 91.63% (very practical). The developed guideline flipbook proved to be very valid and very practical. This guidebook is suitable for use as a guide for implementing Annisa Forum activities at the junior high school level to shape the character and personality of Muslim women.